2021
DOI: 10.5737/23688076313266274
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, utilization and barriers of cervical cancer screening among women attending selected district hospitals in Kigali - Rwanda

Abstract: Background: Cervical cancer is the third most common cancer attacking women globally, and the second in Eastern Africa where Rwanda is located. Regular screening is an effective prevention approach for cervical cancer. Despite that, the screening rate for cervical cancer in Africa is estimated between 10% and 70%, with a number of barriers. This is especially the case in sub-Saharan Africa. In Rwanda, there is limited literature on the rate of use of screening services or the barriers to cervical screening. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
0
27
2
Order By: Relevance
“…Other women noted that they waited until they had health insurance before attendance at screening services. Barrier related to health insurance was previously reported in Rwanda by Niyonsenga et al 18 where 54% of women agreed that lack of health insurance was a barrier for uptake of screening. In the same study, 18 16.6% of participant agreed that there is much money needed for treatment although we can not be sure if they were referring to treatment of cancer or referring to screening cost as the item was described under barrier to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Other women noted that they waited until they had health insurance before attendance at screening services. Barrier related to health insurance was previously reported in Rwanda by Niyonsenga et al 18 where 54% of women agreed that lack of health insurance was a barrier for uptake of screening. In the same study, 18 16.6% of participant agreed that there is much money needed for treatment although we can not be sure if they were referring to treatment of cancer or referring to screening cost as the item was described under barrier to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 82%
“…Prior studies done in different part of Rwanda, although they used different study design to ours, they have reported varying degree of knowledge related to cervical cancer existence, its prevention and screening methods. 17 , 18 , 23 However, none of them has reported health promotion efforts such as the use of SMS, radio station broadcasts, and other telecommunication tools, as possible motivators or sources of information and knowledge related to cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence supports the nding that inequalities in these underserved cervical pre-cancer screening countries favoured women who were older, resided in urban areas, were more educated and in the highest wealth quintile than younger women, who lived in rural areas, were uneducated and in the lowest wealth quintile [9,17,18]. Studies conducted in Ethiopia, Rwanda, Tanzania, Zambia, and Zimbabwe, also support this nding [10,27,28,12,29,11,12,13,14,15]. A study of 18 resource-constrained countries, of which eight were from sub-Saharan Africa further found that wealth status increased socioeconomic inequalities in cervical pre-cancer screening, whereas being married, unemployed and living in urban communities reduced it [9].…”
Section: Discussionmentioning
confidence: 58%